Osaka Triennale : International Contemporary Art Competition : Document 1990-1998 : Sculpture - Painting - Print. - Frank, Basil Colin; Kumagai, Nobuaki; Lee, Jae Hyo; Middendorf, Angelika; Ota, Fusae; Puntusawasdi, Tawatchai; Roman, Mircea; Tillers, Imants; Zhang, Min Jie (Osaka : Osaka Prefectural Government - Osaka Foundation of Culture, 2000)
Allen, Jesse ; Alvarez, Ernesto ; Anatsui, El ; Apichatkriengkral, Wijit ; Barrett, Daniel ; Bedoya, Alfredo Benavidez ; Belik, Jaroslav ; Beltrán, Erick Flores ; Boonyavanishkul, Rearngsak ; Bowen, Dean Leslie ; Cardena, Michel ; Chen, Long Bin ; Chiba, Kentaro ; Choi, Suk-Ho ; Chung, Kyung-Yeun ; Countinho, Graça ; Cuenca, Liliam ; Daré, Salvio ; Dejonghe, Marc ; Dorin, Damaschin ; Dupuy, Jean ; Duval, Barbara ; Effendi ; Escalona, Sydia Reyes ; Faa, Balázs ; Fan, Hui ; Frank, Besil Colin ; Frassi, Giorgio ; Freess, Maike ; Fukumoto, Shigeki ; Gabriely, David ; Gavazzi, Maria Teresa ; Geisel, Jean-Yves ; Gichugu, Meek ; Gilkey, Richard ; Gomez, Victor J. ; Granato, Ivald ; Green, Anthony ; Hamaguchi, Yozo ; Hampson, Mark ; Han, Young-Sup ; Hategan, Florin ; Hertell, Lambert Moraloki & Brigitte ; Hori, Yukiko ; Hunt, Georgina ; Ikeda, Joichi ; Ikeda, Ryoji ; Ikegaki, Tadahiko ; Ikuta, Niyoko ; Inan, Ergin ; Inoue, Hiroko ; Ishibashi, Katsuhisa ; Izuhara, Tsukasa ; Jae-Hyo, Lee ; Jemec, Andrej ; Jie, Zhang Min ; Jolly, Nicholas John ; Jung, Hwan-Sun ; Kamiyama, Akira ; Kanemitsu, Matsumi ; Kasai, Masahiro ; Kasornsuwan, Tinnakorn ; Kawachi, Seikou ; Kazi, Rakib ; Kea-Nam, Cha ; Kenmochi, Kazuo ; Khalil, Mohammad Omer ; Knights, Claire Elizabeth ; Ko-Udomvit, Thavorn ; Kobayashi, Keisel ; Kogan, Leo ; Koizumi, Toshimi ; Komoto, Akira ; Kono, Yoshio ; Konopelska, Elzbieta ; Kosaka, Hirokazu ; Koustas, Apostolos ; Krzysztof, Kris ; Kubo, Akira ; Kubota, Shigeko ; Kumpera, Sophie Daniela ; Kusuda, Shingo ; Laplanche, Geneviève ; Lirata, Kazuyoshi ; Machado, Cabral Graciela ; Makov, Pavel ; Manrique, Maria ; Marhaug, Rita ; Matsumoto, Akira ; Matsumoto, Kaoru ; Matsutani, Takesada ; Michalczak, Kris Krzysztof ; Middendorf, Angelika ; Mohammad, Iqbal ; etc.
biografie
Engels & Japanees
boek